ANALISIS KINERJA MESIN PENGUPAS BIJI KOPI BASAH DENGAN PENGGERAK PULI DAN V-BELT - Angge Christanti B Sinaga; T. Hasballah; Hotmiantua Sitanggang (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2022)
With the existence of a wet coffee bean peeler machine that has been made and the engine performance has been analyzed, the main purpose of making the machine is to simplify and meet the needs of coffee bean peeler machines for farmers throughout Indonesia. With this machine, it is hoped that it can also help the process of stripping coffee beans, making it easier for coffee farmers. The stages in making a coffee bean peeler machine consist of machine design ideas, data collection and then designing a coffee machine product properly so that it can be used as a technical object. Analysis is also needed in terms of machine performance so that the wet coffee bean peeler machine is suitable for use by farmers to facilitate the work of farmers. And the last or final step is to test the feasibility of the tool and after that conclude the results of the wet coffee bean peeler machine. The specifications of this wet coffee bean peeler machine with a capacity of 720 kg/hour, using a 5.5 hp gasoline motor as a driver using a speed of 3600 Rpm, and the frame on the machine using 32 x 32 mm elbows, the type of V belt used is type A 71 and 2 shaft D = 20 mm.